A comparative study regarding face-to-face and online learning approach during the COVID-19 pandemic among Pre-University Students in Malaysia / Azma Abdul Malek ... [et al.] - Abdul Malek, Azma; Muhammad Amin, Siti Noor Syuhada; Aziz, Siti Maisarah; Syed Saadun Tarek Wafa, Sharifah Wajihah Wafa; Zulkifly, Nurul Asma Hasliza; Othman, Aida; Mat Rosid, Salmiah Jamal; Mohammad Yusoff, Nurulhuda; Mohamed, Nurul Najidah; Amzee Zamri, Siti Norziahidayu; Mohamed, Noor Asidah; Ab. Wahab, Fauziah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The coronavirus disease (COVID-19) has caused many fallouts in human daily activities including teaching, learning and examination activities. Students of the Science and Medicine Foundation programme, Universiti Sultan Zainal Abidin (UniSZA), Malaysia, were also affected by the situation where the usual face-to-face (F2F) learning sessions were turned into online sessions. This study aims to examine the impact of online learning on students' academic performance among UniSZA foundation students. It is a retrospective study that involved 251 students who completed the foundation studies between 2020 (intake year 2019/2020) and 2021 (intake year 2020/2021). The mid semester one assessment grades of Biology, Physics, Chemistry, Mathematics, and Information Technology courses were used as the primary comparative factor in assessing performance differences between online and F2F learning. Continuous variables were compared with the independent t-test. A p-value obtained from SPSS that was less than 0.05 (p<0.05) was considered statistically significant. The results showed significant differences in grade performance mean scores for Biology, Physics, and IT subjects compared to Mathematics and Chemistry. The grade performance mean score for Biology was higher in online learning compared to F2F learning. The opposite was noted for Physics and Information Technology subjects where F2F learning showed higher mean scores than online learning. Although there were issues and study limitations, the results show both online learners and F2F learners perform at the same level. This indicates teaching modality may not matter as much as other factors.